Salivary Hormones Response to Preparation and Pre-competitive Training of World-class Level Athletes - Guilhem, Gaël; Hanon, Christine; Gendreau, Nicolas; Bonneau, Dominique; Guével, Arnaud; Chennaoui, Mounir (Frontiers in Physiology, 2015)
This study aimed to compare the response of salivary hormones of track and field athletes induced by preparation and pre-competitive training periods in an attempt to comment on the physiological effects consistent with the responses of each of the proteins measured. Salivary testosterone, cortisol, alpha-amylase, immunoglobulin A, chromogranin A, blood creatine kinase activity and profile of mood state were assessed at rest in 24 world-class level athletes during preparation (3 times in 3 months) and pre-competitive (5 times in 5 weeks) training periods. Total mood disturbance and fatigue perception were reduced, while immunoglobulin A (+61%) and creatine kinase activity (+43%) increased, and chromogranin A decreased (-27%) during pre-competitive compared to preparation period. A significant increase in salivary testosterone (+9 to +15%) and a decrease in testosterone/cortisol ratio were associated with a progressive reduction in training load during pre-competitive period (P < 0.05). None of the psycho-physiological parameters were significantly correlated to training load during the pre-competitive period. Results showed a lower adrenocortical response and autonomic activity, and an improvement of immunity status, in response to the reduction in training load and fatigue, without significant correlations of salivary hormones with training load. Our findings suggest that saliva composition is sensitive to training contents (season period) but could not be related to workload resulting from track and field athletics training.